Circumcision In Ancient Civilizations and Heavenly Religions - Fathi Jawhar Faramzi (QALAAI ZANIST JOURNAL, 2021)
This research deals with the topic of circumcision in ancient civilizations and monotheistic religions, in terms of origin and practice. In order to arrive at the identification of the beginnings of this religious rite, the reasons and motives that led to the practice of circumcision and its motives. The nature of the research necessitated starting by searching for the existence of circumcision in ancient human civilizations, and then searching for it in the divine religions. Through research and investigation, we found that most ancient civilizations practiced circumcision, especially male circumcision. As for female circumcision, it started back to the ancient Egyptians, who practiced female circumcision, known as Pharaonic circumcision. As well as some peoples in Latin America. As for the monotheistic religions, We have found that Judaism has emphasized male circumcision and considered it a divine command, and with regard to female circumcision. There is no text in the Torah that supports female circumcision. Although some Jewish communities practiced female circumcision. In the case of male circumcision was a duty, and for you the Apostle Paul transformed the process of circumcision from a physical act to an act of heart, and said that what is meant by circumcision is not cutting the flesh of the foreskin, but rather what is meant is to remove the malicious intention from the heart. In Islam there were authentic hadiths calling for the practice of circumcision, and they considered it a confirmed Sunnah and that it is part of the innate nature. As for female circumcision, there is no explicit text affirming female circumcision. Rather, its matter is left to necessity and need, and that female circumcision is not a religious matter, rather it is an inherited social custom.